Radiation levels of isolation rooms used by radio-iodine ablation patients during hospitalization - Muhammad Waqar; Touqir Ahmad Afridi; Quratulain Soomro (International Journal of Basic and Applied Science, 2023)
The use of RAI-131 in thyroid carcinoma patients presents a special concern on the environmental radiation safety for those who come in contact with the patients especially after discharge from the facility because of excretion of I131 through perspiration, salivation, breathing and urination. Methods & Materials: The present study was conducted at Nuclear Medicine Oncology and Radiotherapy Institute Nawabshah (NORIN) Sindh from 2017 to 2021 with the objective to evaluate contamination hazards by Excretion made by thyroid cancer patients received iodine therapy stayed in isolation room with doses ranging from 80–200 mCi. The areas included corridor, sink, patient bed, and toilet bowl of isolation rooms before admission and after discharge using LAMSE RM-1001 survey meter. The minimum background radiation level measured before patient stay in isolation room was 0.07 μSv/h while the maximum was 0.40 μSv/h and the mean background reading was 0.18 ± 0.072 μSv/h. The maximum dose rate after discharge was observed at toilet bowl with mean of 9.69 ± 1.98 µSv/hr and minimum of 5.0 µSv/hr and maximum value 13.77 µSv/hr. The readings recorded for the sink were: 2.0 μSv/h minimum, 20.0 μSv/h maximum with a mean of 5.55 ± 1.57 μSv/h while those for the patient bed 0.41 μSv/h minimum, 6.92 μSv/h maximum and a mean of 2.83 μSv/h. the least dose rate was found in isolation room corridor (1.53 ± 0.78 μSv/h) with maximum and minimum values 0.28 & 3.20 μSv/h respectively. Radiation is harmful; safety measures must be ensured to minimize radiation exposure to the family members as well as community either during hospitalization or after discharge of RAI-131 patients. The radiation levels from toilet bowls, beds, sinks, and corridor of isolation rooms were well within the acceptable limits and hence, do not pose significant hazard to the public